Effects of Some Commonly Used COX-1 and COX-2 in the treatment of minor aches on Ovulation in Women A (Clinical Study). - AL-Zohyri, Ahmad M.; Shihab, S S.; Abed, Asmaa N. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Ovulation is the central event in ovarian physiology, and ovulatory dysfunction is a relevant cause of female infertility, (NSAIDs) are consistently inhibit ovulation, likely due to the inhibition of cyclooxygenase that is the rate limiting enzyme in prostaglandin (PG) synthesis.Objectives: The present study was designed to find out the possible restraining influence of some COX-1 and COX-2 drugs on ovulation in women at the child-bearing age and to warn physician of prescribing them to women who want to conceive.Patients and methods:The present study employed in women[52 patients plus 12 controls] attending Baghdad teaching hospital department of rheumatology to assess the influences of some COX-1 and COX-2 NSAIDs [celecoxib, mefenamic acid and ibuprofen on ovulation in women at childbearing age.Results:The present study demonstrated a significant inhibition of ovulation in patients treated with celecoxib , ibuprofen & mefenamic acid and Celecoxib was the highest inhibitor of ovulation compared to the other two drugs ( ibuprofen & mefenamic acid ).a non significant decrease in progesterone level in all three groups in compared to the control group,Functional cyst have been observed in patients treated with celecoxib,and no functional cyst occurs in other two groups treated with mefenamic acid and ibuprofen.Endometerial thickness not affected in all three treated groups.Conclusion: The above findings should be kept in mind and taken in consideration by physicians when they prescribe NSAIDs[Celecoxib,Ibuprofen &mefenamic acid ] to treat female patients at childbearing age due to the inhibitory effects of these drugs on ovulation.